Microbial community composition of transiently wetted Antarctic Dry Valley soils - Niederberger, Thomas D.; Sohm, Jill A.; Gunderson, Troy E.; Parker, Alexander E.; Tirindelli, Joëlle; Capone, Douglas G.; Carpenter, Edward J.; Cary, Stephen C. (Frontiers in Microbiology, 2015)
During the summer months, wet (hyporheic) soils associated with ephemeral streams and lake edges in the Antarctic Dry Valleys (DV) become hotspots of biological activity and are hypothesized to be an important source of carbon and nitrogen for arid DV soils. Recent research in the DV has focused on the geochemistry and microbial ecology of lakes and arid soils, with substantially less information being available on hyporheic soils. Here we determined the unique properties of hyporheic microbial communities, resolved their relationship to environmental parameters and to compared them to archetypal arid DV soils. Generally, pH increased and chlorophyll a concentrations decreased along transects from wet to arid soils (9.0 to ~7.0 for pH and ~0.8 to ~ 5 µg/cm3 for chlorophyll a, respectively). Soil water content decreased to below ~3% in the arid soils. Community fingerprinting-based principle component analyses revealed that bacterial communities formed distinct clusters specific to arid and wet soils; however, eukaryotic communities that clustered together did not have similar soil moisture content nor did they group together based on sampling location. Collectively, rRNA pyrosequencing indicated a considerably higher abundance of Cyanobacteria in wet soils and a higher abundance of Acidobacterial, Actinobacterial, Deinococcus/Thermus, Bacteroidetes, Firmicutes, Gemmatimonadetes, Nitrospira and Planctomycetes in arid soils. The two most significant differences at the genus level were Gillisia signatures present in arid soils and chloroplast signatures related to Streptophyta that were common in wet soils. Fungal dominance was observed in arid soils and Viridplantae were more common in wet soils. This research represents an in-depth characterization of microbial communities inhabiting wet DV soils. Results indicate that the repeated wetting of hyporheic zones has a profound impact on the bacterial and eukaryotic communities inhabiting in these areas.